Anatomical Basis for Malar Augmentation Injection With the Zygomatic Ligamentous System. Issue 10 (12th October 2022) - Duan, Jing; Zhao, Wei-Rui; Luo, Cheng-En; Luo, Sheng-Kang
Abstract : BACKGROUND: The malar augmentation injection has gained popularity in recent years, but the exact location of each injection site has not been clearly identified. OBJECTIVE: To discover ideal injection sites by comprehensively considering the distributions of ligaments, muscles, and vessels. MATERIALS AND METHODS: Eighteen cadaver heads were dissected to investigate the zygomatic ligamentous system and to measure the position of muscles. Sixty-six cadaver heads were subjected to computed tomographic scanning and three-dimensional vessel reconstruction. Radiological evaluation of the fillers was performed before and after experimental injection in one hemiface and dissected to confirm safe delivery. Five patients were enrolled in a prospective clinical study. 2D and 3D photographs were taken before and after the injections for comparison. RESULTS: Site 1 was defined along the zygomatic arch, except the first 1/4 length and the midline of the arch. Site 2 was on the body of the zygoma, superior to the level of the infraorbital foramen and medial to the jugale. Site 3 was defined in the anteromedial midface approximately 30 mm below the lateral canthus. CONCLUSION: Injections at these 3 sites can be performed within the range of the ligaments to achieve effective lifting effects and minimize potential complications.